2018
DOI: 10.1007/s10680-018-9490-4
|View full text |Cite
|
Sign up to set email alerts
|

Who Moves to Whom? Gender Differences in the Distance Moved to a Shared Residence

Abstract: Although the migration of couples and families is well examined, the migration that occurs at the start of co-residence has only been minimally studied. This study examines (1) whether women move more often and move over longer distances at the start of co-residence and (2) whether gender differences (if any) stem from compositional differences between women and men, such as gender differences in ties, or if they are the consequence of the within-couple distribution of bargaining power. The analyses are perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 65 publications
3
47
0
Order By: Relevance
“…Fourth, the distance to family members might influence the distance between partners before living together. Swedish men tend to live closer to their parents than Swedish women do (Brandén and Haandrikman, 2013;Malmberg and Pettersson, 2007), and couples with children tend to live closer to the paternal than to the maternal grandparents (Løken et al, 2013). For the present study, I expect that spatial homogamy is strongest in urban areas and for people living close to family members, but that distances between partners before co-residence are longer for mobile individuals.…”
Section: Factors Influencing Spatial Homogamymentioning
confidence: 80%
See 1 more Smart Citation
“…Fourth, the distance to family members might influence the distance between partners before living together. Swedish men tend to live closer to their parents than Swedish women do (Brandén and Haandrikman, 2013;Malmberg and Pettersson, 2007), and couples with children tend to live closer to the paternal than to the maternal grandparents (Løken et al, 2013). For the present study, I expect that spatial homogamy is strongest in urban areas and for people living close to family members, but that distances between partners before co-residence are longer for mobile individuals.…”
Section: Factors Influencing Spatial Homogamymentioning
confidence: 80%
“…Another could be that, with age, women in particular place more value on socio-economic status in partner choice (Schwarz and Hassebrauck, 2012), which may imply longer distances to find such a partner. Third, women more often move longer distances than men, because men (who are generally a few years older than their partners) are more established in the labor and housing market than women of a similar age (Bielby and Bielby, 1992;Mulder and Malmberg, 2012), and because of a gender culture that supports the systematic adaptation of women to their partners' careers (Brandén and Haandrikman, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Other research highlights relevant gendered patterns in spatial mobility that are substantial at the time of union and family formation and thereafter (Brandén and Haandrikman 2018). The pervasive and persistent gender inequalities in the labour market that permeate spatial mobility decisions are particularly relevant to the labour outcomes of men and women in family households.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research suggests that in the Netherlands, married couples are living closer to the parents of the husband than the parents of the wife (Blaauboer et al, ). A study from Norway found—to the surprise of the researchers—that married couples reside closer to the husband's than the wife's parents (Løken et al, ), and a Swedish study similarly found that females where more likely to move to the male's place when couples started a coresidential union (Brandén & Haandrikman, ). Other studies using register data from the Nordic countries indicate that men are more likely than women to live close to their ageing parents, contrary to the cultural expectations about adult daughters acting as carers for their parents (e.g., Malmberg & Pettersson, ).…”
Section: Introductionmentioning
confidence: 99%